1985
DOI: 10.1063/1.865198
|View full text |Cite
|
Sign up to set email alerts
|

Trapped particle destabilization of the internal kink mode

Abstract: This report was praparad as an-account of worJe sponsored ay the Unitad Stat as Govamfflent. Neither the CJnited Scares nor she United Sfcatas Dipartaent of Energy, nor r-'. of thair «ploy««s, nor any of -aeir contss Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 14 publications
8
100
0
Order By: Relevance
“…Here, we emphasize that unlike the previous analysis [9][10][11][12][13] the stability window exists even in the absence of core ion finite Larmor radius v9ffect (finite Ol.i).…”
Section: Effects Of Neutral-beam-injected Particles On the N=1 Internmentioning
confidence: 61%
See 3 more Smart Citations
“…Here, we emphasize that unlike the previous analysis [9][10][11][12][13] the stability window exists even in the absence of core ion finite Larmor radius v9ffect (finite Ol.i).…”
Section: Effects Of Neutral-beam-injected Particles On the N=1 Internmentioning
confidence: 61%
“…We should reiterate here that the first (to./cod) term in Eq. (24) does not cancei with the hot particle contribution to y B , Equation (24) , there is a stability window for P h1 <$u< Ph2-It is important to note that previous studies [9][10][11][12][13] have concluded that Phi -Ph2 so that there is no stability window. The erroneous conclusion is mainly due to the mistake of making exact cancellation of the first (oo./<fld) term in Eq.…”
Section: Analytic Dispersion Relation For the N=1 Interna! Kink Modementioning
confidence: 99%
See 2 more Smart Citations
“…Most previous work [10][11][12][13] used analytic methods valid for large aspect ratio circular tokamaks. General shaped tokamak equilibria have been considered in a few studies only [14][15][16].…”
Section: Introductionmentioning
confidence: 99%